Derivation of turbulent energy dissipation rate with the Middle Atmosphere Alomar Radar System (MAARSY) and radiosondes at Andøya, Norway - Li, Qiang; Rapp, Markus; Schrön, Anne; Schneider, Andreas; Stober, Gunter (Annales Geophysicae, 2016)
We present the derivation of turbulent energy dissipation rate " from a total of 522 days of observations with the Middle Atmosphere Alomar Radar SYstem (MAARSY) mesosphere–stratosphere–troposphere (MST) radar running tropospheric experiments during the period of 2010–2013 as well as with balloon-borne radiosondes based on a campaign in the summer 2013. Spectral widths are converted to " after the removal of the broadening effects due to the finite beam width of the radar.